Pemulihan Hak-Hak Korban Penyiksaan di Tahanan Kepolisian Sektor Sijunjung, Sumatera Barat - Refki Saputra (Jurnal Cita Hukum, 2016)
Abstract: Acts of torture are still rife in Indonesia. Protection of the victim to be one of the thorny issues in the act of torture. Since the reform era, there are certain rules and institutions that affect the regime of protection of victims in Indonesia, but not enough to provide protection for victims of torture. In addition to the lack of legal instruments that specifically regulates matters of acts of torture, the perception of inequality among law enforcers is also a major obstacle to the healing process rights of victims of torture. Absence of regulations explicitly declare torture as a crime and violation of human rights can not be postponed again. Because the torture emerged from an authority given by the state as a law enforcer, but lack of control. The victims are in a very vulnerable side for dealing with the state as an actor and also law enforcement. LPSK as an independent state institution has a great opportunity to overcome the imbalances which in essence gives a more real justice for victims.